Analisis Kadar Vitamin C Mangga Gadung (Mangifera sp) Dan Mangga Golek (Mangifera indica L) Berdasarkan Tingkat Kematangan Dengan Menggunakan Metode Iodimetri - Rahman, Nurdin; Ofika, Mairet; Said, Irwan (Universitas Tadulako, 2015)
Mango fruits contain several nutrients which are beneficial for the improvement of people’s nutrition. Vitamin C is one of which highly needed by the body and can be used as a source of antioxidants. Vitamin C level of mangoes is strongly influenced by their varieties, environments, places, fertilizers, maturity levels, and so on. Levels of vitamin C will increase until the fruit is ripe, and will decrease when the maturity level has been exceeded. This research determined the vitamin C level of gadung and golek mangoes based on the maturity levels. gadung and golek mangoes used as the samples were half-ripe, ripe, and overripe fruits. Analysis of vitamin C levels in the samples was done by iodimetry method. The results showed that the vitamin C levels of Gadung were 83.66 mg/100 g on the half-ripe fruits, 101.82 mg/100 g on the ripe fruits, and 92.85 mg/100 g on the overripe fruits. Whereas the vitamin c levels of golek were 57.72 mg/100 g on the half-ripe fruits, 79.30 mg/100 g on the ripe fruits, and 61,14 mg/100 g on the overripe fruits. The data indicate that the ripe fruits of mangoes contain the optimum level of vitamin C.